Cognition, Structural Brain Changes, and Systemic Inflammation in Adolescents Living With HIV on Antiretroviral Therapy. (1st May 2020) - Hoare, Jacqueline; Myer, Landon; Heany, Sarah; Fouche, Jean-Paul; Phillips, Nicole; Zar, Heather J.; Stein, Dan J.
Abstract : Objective: To investigate the association between neurocognitive impairment, neuroimaging, and systemic inflammation in perinatally infected adolescents living with HIV (PHIV) on antiretroviral therapy (ART). Systemic inflammation may be one mechanism driving neurocognitive impairment despite ART, but this has not been investigated in adolescence when the brain is undergoing rapid development. Setting: Cape Town, South Africa. Methods: Baseline data were drawn from the Cape Town Adolescent Antiretroviral Cohort. PHIV on ART >6 months completed a comprehensive neurocognitive test battery. Diffusion tensor imaging and structural brain magnetic resonance imaging was done to determine whole brain fractional anisotropy, mean diffusion (MD), grey and white matter volumes, and cortical thickness. We examined how neurocognitive and neurostructural measures were associated with a concurrently measured marker of systemic inflammation, high-sensitive C-reactive protein (hs-CRP). Results: One hundred sixty-eight PHIV ages 9–12 years (mean CD4 980 cells/µL; 85.3% viral load <50 copies/mL) and 43 controls were included in the analysis. PHIV had similar hs-CRP ( P = 0.17) to controls, after participants with hs-CRP >10 were excluded from the analysis. Forty-eight percent of the PHIV in this analysis have a neurocognitive disorder. Whole brain grey ( P = 0.049) and white matter volumes ( P = 0.044) were lowest in PHIV with a major neurocognitive disorder. Higher MD, was found in PHIV with a major neurocognitive disorder ( P = 0.002). Among PHIV with a neurocognitive disorder, hs-CRP negatively correlated with general intelligence, visual spatial acuity, and executive function (all P = < 0.05). Whole brain MD correlated with higher hs-CRP values ( P = < 0.01) in PHIV. Conclusions: A marker of systemic inflammation was associated with both neurocognitive impairment and MD increases in PHIV.